Christian philosophy : a systematic and narrative introduction - Bartholomew, Craig G., 1961-; Goheen, Michael W., 1955- (2013)
"Christian Philosophy offers a comprehensive narrative of philosophical thought from a distinctly Christian perspective. After exploring the interaction among Scripture, worldview, theology, and philosophy, Craig Bartholomew and Michael Goheen tell the story of philosophy from ancient Greece through postmodern times, positioning the philosophers in their historical contexts and providing Christian critique along the way. The authors emphasize the Reformed philosophical tradition without neglecting other historical trajectories and show how philosophical thought relates to contemporary life" -- BACK COVER
Why philosophy? -- Faith and philosophy -- Ancient pagan philosophy : the Pre-Socratics to Socrates -- The high point of Greek philosophy : Plato, Aristotle, and their legacy -- Medieval synthesis philosophy : Augustine to Abélard -- The Middle Ages : Aristotle rediscovered -- The Renaissance and Reformation -- Early modern philosophy : Bacon to Leibniz -- Modern philosophy : Hume to Schleiermacher -- Modern philosophy : romanticism to Gadamer -- Postmodernism and philosophy today -- Christian philosophy today -- Reformed epistemology -- Reformed epistemology applied -- Reformational philosophy
Includes bibliographical references (pages 271-278) and index
Keywords: Christian philosophy